Ramie fabric Elium® composites with flame retardant coating: Flammability, smoke, viscoelastic and mechanical properties. (October 2020) - Khalili, Pooria; Blinzler, Brina; Kádár, Roland; Blomqvist, Per; Sandinge, Anna; Bisschop, Roeland; Liu, Xiaoling
Highlights: Enhancement of flame retardancy and smoke suppressant of natural fibre Elium® composite laminates using intumescent thermal resistive mats containing expandable graphite was performed successfully. While higher expansion ratios of EG particles in the composite lead to greater flame resistivity and reduction of smoke, the modulus decrease proportional to the increase of EG exfoliation ratio. The bending strength of composites was found to increase as compared to that of the Control composite and the glass transition temperature was seen to increase with EG of lower expansion ratios in the coating material. Abstract: This investigation studied the utilization of intumescent thermal resistive mats to provide surface protection to the core natural fibre-reinforced Elium® composite structural integrity. The intumescent mats contained flame retardant (FR) i.e. expandable graphite (EG) with four different expansion ratios and alumina trihydrate (ATH). All natural fibre thermoplastic composites were fabricated using a resin infusion technique. The impact of char thickness and chemical compositions on the flammability and smoke properties was investigated. It was found that surface protection significantly reduced the peak heat release rate, total smoke release, smoke extinction area and CO2 yield, and substantially enhanced UL-94 rating, time to ignition and residual char network, depending on the EG exfoliation ratio, ATH and mineral wool fibre. The glass transition temperature increased for the FR composites containing EG with lower expansion ratio. Inclusion of intumescent mats increased the strength of the composites while it had a negative effect on the modulus.